Choice Of Nation State And The Implications For Indonesian Islam - Taufik Nugroho; Nashrul Muminin; Ika Kartika Sari; Sahril Fadli; Ramli Umar (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2026)
This study examines the opposition of some Indonesian Muslims to the nation-state, which they consider a failure because it does not utilize Islam or Islamic law as the foundation of the state. Consequently, Pancasila is questioned as an ideology. This qualitative research used interviews and observations, using primary data from organizational archives and government policies, as well as secondary data from Islamic political studies. The results indicate that development programs are perceived as marginalizing Islamic values ​​and limiting the implementation of Islamic law, thus creating religious discomfort. In conclusion, this opposition reflects the incomplete transition of some Muslims from the idea of ​​a caliphate to a nation-state. In a pluralistic nation-state, Muslims are required to accept diversity and equality of all components of society without discrimination.